2014
DOI: 10.1517/13543784.2014.884708
|View full text |Cite
|
Sign up to set email alerts
|

A new dawn for the use of thiazolidinediones in cancer therapy

Abstract: Various preclinical and clinical studies strongly suggest a role for TZDs both alone and in combination with existing chemotherapeutic agents, for the treatment of cancer. The exploration of newer TZDs at different doses, as well as developing partial agonists, can potentially help in unveiling the underlying mechanisms of these therapeutics, and consequently, treat this dreadful group of diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…This novel information may have important implications for the responsiveness of different disease types to treatment with these compounds. The dual action of PPAR agonists may also account for the variable effects of PPAR activation in the treatment and development of distinct tumor entities [3638]. It is possible that the activation status of the cancer cells or tumor stromal cells, including macrophages, fibroblasts, endothelial cells, and others, may influence PPAR function.…”
Section: Discussionmentioning
confidence: 99%
“…This novel information may have important implications for the responsiveness of different disease types to treatment with these compounds. The dual action of PPAR agonists may also account for the variable effects of PPAR activation in the treatment and development of distinct tumor entities [3638]. It is possible that the activation status of the cancer cells or tumor stromal cells, including macrophages, fibroblasts, endothelial cells, and others, may influence PPAR function.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this suggests that PPAR activation is involved in the anti‐tumour effects of cannabinoids. In support of this, there is increasing evidence that the thiazolidinedione class of PPARγ ligands, normally used in the treatment of diabetes, may have a potential new role in the treatment of cancer (Joshi et al , ).…”
Section: Physiological Responses To Cannabinoids Mediated By Pparsmentioning
confidence: 97%
“…Among the synthetic ligands, thiazolidinediones, a class of medications originally used for the treatment of type 2 diabetes mellitus, have been widely investigated as anti–lung cancer agents. The administration of thiazolidinediones for anticancer therapy is known to produce some side effects . Moreover, recent studies have further shown that the prolonged use of thiazolidinediones is associated with an increased risk of bladder cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The administration of thiazolidinediones for anticancer therapy is known to produce some side effects. 16 Moreover, recent studies have further shown that the prolonged use of thiazolidinediones is associated with an increased risk of bladder cancer. 17 These adverse effects have limited the therapeutic application of synthetic PPARc ligands.…”
Section: Introductionmentioning
confidence: 99%